Preoperative anxiety and its associated factors among patients undergoing cardiac catheterization at saint peter Specialized Hospital and Addis Cardiac Center, Addis Ababa, Ethiopia - Neway Afrassa; Rahel Nega Kassa; Tesfaye Girma Legesse (Elsevier, 2022)
Background: Hospitalization and surgery are critical, negative life events that lead to a significant number of patients with anxiety. There is a study gap regarding preoperative anxiety status and factors associated with patients undergoing cardiac catheterization in Ethiopia. Objective: To assess preoperative anxiety and its associated factors among patients undergoing cardiac catheterization at Saint Peter specialized hospital and Addis Cardiac Center, Addis Ababa, Ethiopia. Methods: A cross-sectional study design was conducted among 267 cardiac patients admitted and scheduled to undergo cardiac catheterization at St. Peter and Addis Cardiac Center from March to June 2021. Data were collected by an interviewer-administered, standardized, and structured questionnaire. Then the data were entered into EPI data version 3.1 and analyzed by SPSS version 25. The multivariable logistic regression model was fitted to identify factors associated with preoperative anxiety among patients undergoing cardiac catheterization at 95% CI. The result was presented in tables, graphs, and statements. Result: The prevalence of preoperative anxiety among patients undergoing cardiac catheterization was 70.4% [95% CI (65.0-75.7%)]. Government employee [AOR, 3.38 (95% CI: 1.45, 7.68)], private employee [AOR, 5.84 (95% CI: 2.35, 14.51)], history of previous surgery [AOR, 0.47 (95% CI: 0.23, 0.94)], searching support [AOR, 3.03 (95% CI: 1.56, 5.88)] and listening to music [AOR, 0.50 (95% CI: 0.26, 0.96)] as coping mechanism were significantly associated with high preoperative anxiety. Conclusion: Preoperative anxiety is a highly prevalent and significant public health problem among patients undergoing cardiac catheterization in the study area. Recommendations: Regular anxiety counseling, facilitating, and adhering to preoperative anxiety coping mechanisms are protective.